Photoluminescent carbon nanodots: synthesis, physicochemical properties and analytical applications - Roy, Prathik; Chen, Po-Cheng; Periasamy, Arun Prakash; Chen, Ya-Na; Chang, Huan-Tsung (Materials today (Kidlington, England), 2015)
Carbon nanodots (C-dots) possessing photoluminescence (PL) properties have become interesting materials for sensing and imaging, with the advantages of water-dispersibility, biocompatibility, chemical and photo stability. They can be prepared from organic matter such as tea, grass, coffee, and small organic molecules like glycine and glucose through hydrothermal routes. In this review, we focus on the recent advances in the synthesis and characterization of C-dots along with their optical (absorption, PL, upconverted PL) properties and analytical applications. Having bright PL, biocompatibility, chemical and photo stability, as well as low toxicity, C-dots have been used for the detection of metal ions and for cell imaging. C-dots prepared from organic matter such as used tea and ginger possess a great inhibitory effect on the growth of cancer cells, showing their excellent potential as new drugs.